Bilingual Education APathway to Enhance Students’ Research Skills in Elobeid Town of North Kordofan State, Sudan - Mahasin Basheir M. Sirag Eldden; Elzain Musa Jumaa Elimam; Abdealrahman Elsherief Hamed; Magzoub Elsaeid Ahmed (IJRDO- Journal of Educational Research, 2020)
The current study was conducted in Elobeid town at the Faculty of Education University of Kordofan during 2019-2020.The objective of the study was to know the role of bilingual education in enhancing students’ research skills, the most important factor of success in bilingual education, interpret and analyze the role and significant of bilingual education in promoting and enhancing students research skills. Primary data were collected via structured questionnaire following random sampling technique (48) respondents representing 27% of the total English language teachers (185).Descriptive statistical analysis was used for data analysis. The results showed that a lot of teachers agreed that bilingual education enhance students research skills (62.5%), the effectiveness of bilingual education focus on both the language of instruction and models (79.1%), bilingual education means finding various pedagogical theories for practical usage (77.1%),the good teacher should have sufficient knowledge on other field to promote the student research study (93.7%).the most important factor of success in bilingual education is motivation (87.5%). The study concluded that, bilingual education is essential in enhancing students’ research skills and it needs motivation. The study recommends the important of using bilingualism in teaching any foreign language.